2004
DOI: 10.1002/jbm.b.30029
|View full text |Cite
|
Sign up to set email alerts
|

Use and re‐use of orthopedic implants in developing countries

Abstract: A de novo 3‐bp deletion (179–181delGTG) was identified at exon 3 of the PTPN11 gene in a female infant with severe Noonan phenotype including hydrops fetalis and juvenile myelomonocytic leukemia. Since the 3‐bp deletion is predicted to result in loss of the 60th glycine in the N‐SH2 domain that is directly involved in the intramolecular interaction between the N‐SH2 and the PTP domains of the PTPN11 protein, this mutation would disrupt the N‐SH2/PTP binding in the absence of a phosphopeptide, leading to an exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Literature does not provide scientific evidence and practical arguments to forbid the reuse of orthopedic plates and screws and it is well possible that under certain circumstances reuse is acceptable. From practical experience and oral communications, we know that in different developing countries, for instance Indonesia, Afghanistan, Kenya, and Surinam, explanted plates and screws are being reused and reinserted into other patients 2. In the Western world, ever‐rising health care costs occasionally point to reuse of single use devices as an option to reduce health care costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature does not provide scientific evidence and practical arguments to forbid the reuse of orthopedic plates and screws and it is well possible that under certain circumstances reuse is acceptable. From practical experience and oral communications, we know that in different developing countries, for instance Indonesia, Afghanistan, Kenya, and Surinam, explanted plates and screws are being reused and reinserted into other patients 2. In the Western world, ever‐rising health care costs occasionally point to reuse of single use devices as an option to reduce health care costs.…”
Section: Introductionmentioning
confidence: 99%
“…From practical experience and oral communications, we know that in different developing countries, for instance Indonesia, Afghanistan, Kenya, and Surinam, explanted plates and screws are being reused and reinserted into other patients. 2 In the Western world, ever-rising health care costs occasionally point to reuse of single use devices as an option to reduce health care costs. The United States Food and Drug Administration (FDA), in a study on cost-effectiveness, showed that the reuse of single use devices could reduce hospital and patients costs by 34 and 32%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Stability at high temperature: Maintaining the cold chain can be difficult in many developing countries. Thus, biomaterials designed for these countries should also be able to resist prolonged exposure to temperatures of 40°C or more as frequently observed during transportation of medical supplies in developing countries. Robustness: Biomaterials should be designed to be robust as the replacement or repair of a deficient biomaterial is even more difficult in developing countries because of the cost involved and lack of facilities and medical staff. No need for repeated visit for implantation or use: Similar reasons as above. Biohazards: Biomaterials for developing countries should ideally be easy to discard without contributing to the growing problem of biohazards disposal as many medical facilities in these countries might not be well equipped to properly dispose of biohazards. Reuse: To reduce costs, biomaterials are often reused in developing countries 12. Thus, it might be useful for some specific applications to design biomaterials that can be easily and safely reused.…”
mentioning
confidence: 99%
“…Reuse: To reduce costs, biomaterials are often reused in developing countries 12. Thus, it might be useful for some specific applications to design biomaterials that can be easily and safely reused.…”
mentioning
confidence: 99%
See 1 more Smart Citation